PENGARUH ANALISIS RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR DI BEI - Renantha Renantha; Tony Sudirgo (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to obtain empirical evidence about the effects of current ratio, return on assets, total asset turnover, and sales growth on financial distress. This research is conducted by taking 78 manufacturing companies which listed on Indonesian Stock Exchange on 2017-2019. The sample selection technique used is purposive sampling. Data processing techniques using multiple regression analysis that helped with E-views 10.0 program. The result showed current ratio, return on assets, and total asset turnover have a significant impact on financial distress while the other variable, sales growth showed an insignificant impact on financial distress. The implication of this study is the need to decrease the liabilities also to increase the sales and income that will decrease the financial distress which will bring a good signal for investors.